The Combination of 18F-Fluorodeoxyglucose Positron Emission Tomography Metabolic and Clinical Parameters Can Effectively Distinguish Rheumatoid Arthritis and Polymyalgia Rheumatic. (11th April 2022) - Wang, Guanyun; Liu, Xiaofei; Chen, Jiaxin; Zhang, Fengyan; Xu, Xiaodan; Wang, Yanmei; Wang, Ruimin; Yao, Shulin; Zhu, Jian; Guan, Zhiwei
Abstract : Objective . To evaluate 18 F-fluorodeoxyglucose positron emission tomography ( 18 FDG PET) and clinical parameters to differentiate rheumatoid arthritis (RA) and polymyalgia rheumatic (PMR). Patients and Methods . This retrospective study evaluated 54 patients with suspected RA ( n  = 23) and PMR ( n  = 31) who underwent 18 F-FDG PET/CT before treatment. The complete diagnosis was based on each classification criterion and at least followed up for 6 months. Demographic and clinical data were also collected. Semiquantitative analysis (maximum standardized uptake value, SUVmax) of abnormal 18 F-FDG uptake was undertaken at 17 musculoskeletal sites, and two scoring systems (mean reference (liver/control) scores) were evaluated. The differential diagnostic efficacy of each independent parameter was evaluated using the receiver operating characteristic (ROC) curve. Integrated discriminatory improvement (IDI) and bootstrap tests were used to evaluate the improvement in diagnostic efficacy using a combination of multiple parameters. Results . The ROC curve analysis of SUVmax indicated that the interspinous ligament showed the highest discriminative diagnostic value (sensitivity, 64.5%; specificity, 78.3%; area under the curve (AUC), 0.764; positive predictive value, 0.800; negative predictive value, 0.621). The combined model with the rheumatoid factor (RF) and metabolic parameters of 18 F-FDG PET resulted in the highest AUC of 0.892 and showed significant reclassification by IDI (IDI, 9.51%; 95% confidence interval: 0.021–0.175; P  = 0.013). According to the bootstrap test, compared with RF alone, the combination of RF and metabolic parameters showed an improvement in ROC and was statistically significant ( P  = 0.017). Conclusions . The combination of 18 F-FDG PET metabolic and clinical parameters can further improve the differential diagnosis of RA and PMR.